Permasalahan Manajemen Kelembagaan Yang Menyebabkan Kurangnya Motivasi Belajar Di PKBM Permai - Sani Susanti; Anugrah Setiawan; Delli Suci; Fatma Pane; Marisa Nabila; Oriza Salsabila; Thomas Thomas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines problems in institutional management that cause low learning motivation among students at PKBM Permai. Motivation to learn is one form of success in the learning process. The research method used is qualitative, with a descriptive method with data collection through observation, namely making direct observations at PKBM Permai, then conducting in-depth interviews with heads of institutions, and documentation to record and maintain accurate and organized records about an event, process or information. certain. The findings reveal that one of the causes of low motivation to learn is due to age factors, inadequate facilities and infrastructure and tutors not being suitable in their field. This study also shows that tutors who are not suited to their field can cause problems, so there is a need for continuous professional development for tutors to improve the quality of education